2005
DOI: 10.1038/sj.ejcn.1602099
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of human milk in Western Iran

Abstract: Objective: To investigate the fatty acid composition of mature human milk in Western Iran with special focus on trans fatty acids. Design: Observational study. Methods: Milk samples were collected from 52 lactating mothers aging 19-39 y, from Western Iran. Subjects were asked to complete a diet questionnaire. Milk fatty acids were measured as 2-nitrophenylhydrazide derivatives by high-performance liquid chromatography. Results: Saturated fatty acids were the main fraction of human milk (41.3%). Medium-chain fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
19
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
7
19
2
1
Order By: Relevance
“…A 2005 study in Iran found that increased maternal intakes of trans fatty acids leads to increased amounts of trans fatty acids in the breastmilk (Bahrami and Rahimi, 2005). Other studies have also reported strong correlations between maternal and infant plasma trans fatty acid concentrations (Koletzko and Muller, 1990;Craig-Schmidt, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2005 study in Iran found that increased maternal intakes of trans fatty acids leads to increased amounts of trans fatty acids in the breastmilk (Bahrami and Rahimi, 2005). Other studies have also reported strong correlations between maternal and infant plasma trans fatty acid concentrations (Koletzko and Muller, 1990;Craig-Schmidt, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Aihaud et al (2006) have also attributed the risk of breastmilk to overweight and obesity in later life to its fatty acid content. The fatty acid composition of human milk is reported to be influenced by maternal dietary fatty acid composition (Anderson et al, 2005;Bahrami and Rahimi, 2005;Koletzko et al, 2005). Although the fatty acid composition of infant formula differs from breastmilk, it remains constant over time, whereas the fatty acid composition of human milk varies greatly from one mother to another and even within a breastfeeding episode (Koletzko and Rodriquez-Palmero, 1999;Koletzko et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. While the naturally occurring isomers have mainly cis configuration, trans fatty acids appear naturally in milk [1,2] and can be artificially produced by heating and hydrogenation of vegetable oils [3]. Investigation of function and possible adverse effects of trans fatty acids on human health have been carried out extensively in recent years [4,5].…”
mentioning
confidence: 99%
“…A recent report indicates that the mean level of TFA consumption in Iran, as compared to the level in most of other countries, is high [16] . This difference may be attributed to the hydrogenated oils available in Iran that carry large amounts of TFA.…”
Section: Introductionmentioning
confidence: 99%